The Implementation of Read Aloud Through Virtual Meeting on EFL Primary Students in Thailand - Mega Fuji Rahayu; Prativi Khilyatul Auliya (STKIP PGRI Lubuklinggau, 2021)
This study aims at finding out the implementation of reading aloud through virtual meetings on EFL primary students. Students have one month to use the zoom meeting application as medium to implementing read aloud. The design of this study is qualitative method using observation, questionnaire checklist, and interview. The subjects of this study were grade 4 students at Nongekeng school, Thailand. The results from data analysis show that there is positive response from students during the implementation of reading aloud using the zoom virtual meeting. Students can focus more on learning, be active in class, have good attitude, good pronunciation and intonation of reading, and ask questions confidently. However, there are obstacles during the teaching process such as an internet connection. But it can be handled well, so the implementation of reading aloud through virtual meeting is worth to use during pandemic situation like this.